Multistage treatment of lung cancer patient: a case report - Tomaszewski, Dariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The treatment of some complications after pneumonectomy is prolonged and multistage. Lung cancer recurrence after pneumonectomy is a rare indication for radical treatment. The case we report was treated surgically for primary lung cancer seven years ago. Empyema after pneumonectomy appeared twice and required multistage treatment. At the same time the patient underwent additional pulmonary resection for cancer recurrence in the remaining lung. In these cases radical surgery or oncological treatment is almost always impossible. The patient we describe is still alive without any complications or recurrence of cancer.